PENGGUNAAN INSTAGRAM @BDG.SIAGA113 SEBAGAI MEDIA INFORMASI KESIAPSIAGAAN BENCANA - Mahesa, Azka Raihan; Dama, Muhammad Satrian Duva (eProceedings of Management, 2024)
This research reviews the Using Instagram @bdg.siaga113 as a Preparedness Information Media. The city ofBandung is one of the cities in Indonesia that has a high potential for disasters. The existence of fast and accurateinformation media is very important in disaster management. Social media Instagram @bdg.siaga113 is one of themedia used by the Bandung City Fire and Rescue Department to convey emergency information to the public. Thisthesis aims to analyze the disaster communication strategy of the social media Instagram @bdg.siaga113 as a mediafor emergency information in the city of Bandung. The research method used is qualitative with a descriptiveanalytical approach. Data collection techniques were carried out through social media observations, in-depthinterviews, as well as business communication strategy concepts from (Haddow & Haddow, 2022). The researchresults show that Instagram @bdg.siaga113 has not made maximum efforts in disaster communication strategies.There are five disaster communication strategy concepts consisting of customer focus, leadership commitment,communication Planning and Operations, situasional awareness and media partnership. Kata Kunci: Komunikasi Bencana, Kegawatdaruaratan Kota Bandung, Media Social